Minimal Spillover of Native Small Mammals From Bornean Tropical Forests Into Adjacent Oil Palm Plantations - Chapman, Philip M.; Loveridge, Robin; Rowcliffe, J. Marcus; Carbone, Chris; Bernard, Henry; Davison, Charles W.; Ewers, Robert M. (Frontiers in Forests and Global Change, 2019)
In the face of rapid tropical agricultural expansion, preservation of tropical forest remnants is crucially important. Forest remnants often abut the edges of new or established plantations, so landscape-level conservation requires an understanding of the balance between ecosystem services and disservices provided by forest, including potential crop yield reductions caused by species such as rodents, an important pest group in oil palm plantations. However, very little is known about the scale of any spillover of native species which inhabit forest into adjacent agricultural areas. We examined the distribution and behaviour of small mammals across an edge separating logged tropical forest and oil palm plantations in Sabah, Malaysian Borneo, using a dual approach. We used a trapping grid to reveal patterns of species relative abundance across the forest-plantation edge, and tracked individuals of forest species using a spool-and-line. We uncovered little evidence that the native forest small mammal community crosses the edge and uses the plantation, although two invasive small mammal species were found across the whole edge gradient. Of 10 forest species detected, we found only the adaptable murid Maxomys whiteheadi in the plantation, where it persisted at low abundances across all sampling points, including in the plantation interior control site. This pattern is more consistent with persistence of M. whiteheadi throughout plantations than with spill-over from forest fragments. On the forest side, observed species richness of small mammals increased with distance into the interior, suggesting a negative edge effect may exist within forest remnants. Of 23 successfully tracked small mammals, only one M. whiteheadi crossed the forest-plantation edge, and overall, this species was significantly repelled from crossing into plantation habitat. Our results suggest that spillover of native small mammals contributes little to oil palm damage close to forest-plantation edges, but that oil palm negatively impacts small mammal populations within adjacent forest remnants.